The relevance assessment of the land use for wind power engineering in settlements of Lviv region - Sai, Vira; Кhavar Yulia; Vynarchyk, Liliya (Geodesy and Cartography, 2019)
The aim of the work is to study the relevance of new wind power facilities installation for electricity production in the Lviv region. In this paper, all the necessary conditions for the construction of wind power plants are considered. Analysis of the preferred land plot choice for wind energy generation due to favorable wind conditions and limited environmental impact is carried out. The wind turbines with the capacities, which are most appropriate to use in this region, were selected, as well as the environmental impact of the wind power plants is defined. It is proved that it is advisable to use wind turbines of the type “ECO 100” with a capacity of 3.0 MW. The results of the research can be effectively used by design and production organizations in the management of geodetic monitoring of the wind power plants state.